Key analysis of the hill cipher algorithm (Study of literature) - Sujarwo, Sujarwo (Jurnal Mandiri IT, 2024)
The security of the data (message) sent is very important in maintaining the confidentiality of the message. Many algorithms can be used to secure messages. Among them is the Hill Cipher algorithm. The Hill Cipher algorithm is a classic cryptographic algorithm. This algorithm uses a square matrix key. In connection with the Hill Cipher algorithm key, this literature aims to examine the matrix that can be used as a key in the encryption and decryption process in the Hill Cipher algorithm. In this literature, we take a square matrix of order 3x3 and use 36 characters (A-Z, 0-9). To produce cipher text, the method used is to carry out an encryption process based on the Hill Cipher algorithm. The encryption process is carried out by multiplying the key matrix by the plaintext. The decryption process to get the plain text back is done by multiplying the ciphertext by the inverse modulo matrix of the key matrix. The encryption process can always be carried out, but not all decryption processes can be carried out. Because not all matrices can be used as key matrices. The results of this literature show that the key matrix must be a matrix of order mxm. A matrix with determinant value = 0 cannot be used as a key. Likewise, a matrix whose determinant value is not relatively prime with the number of characters to be encrypted or decrypted cannot be used as a key matrix